2020
DOI: 10.1039/d0ob00579g
|View full text |Cite
|
Sign up to set email alerts
|

Chemo- and regioselective click reactions through nickel-catalyzed azide–alkyne cycloaddition

Abstract: Nickel-catalyzed [3 + 2] cycloaddition reactions of unsymmetrical alkynes and organic azides afford substituted 1,2,3-triazoles with high levels of chemo- and regioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…We found that the present heterogeneous catalytic system offers certain advantages like easy preparation from cheap and sustainable materials, stable at room temperature, high catalytic efficiency in aqueous medium, regioselective formation of 1,4-disubstituted-1,2,3triazoles, recovery by simple filtration and recyclability. As compared to previously reported very few homo-and heterogeneous Ni-based catalysts used in AAC, [13][14][15][16] the present catalytic process using Ni-rGO-zeolite follows three-component cycloaddition, which is more advantageous over two-component cycloaddition process because the former avoids an extra step of making unstable organyl azides (Scheme 1).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…We found that the present heterogeneous catalytic system offers certain advantages like easy preparation from cheap and sustainable materials, stable at room temperature, high catalytic efficiency in aqueous medium, regioselective formation of 1,4-disubstituted-1,2,3triazoles, recovery by simple filtration and recyclability. As compared to previously reported very few homo-and heterogeneous Ni-based catalysts used in AAC, [13][14][15][16] the present catalytic process using Ni-rGO-zeolite follows three-component cycloaddition, which is more advantageous over two-component cycloaddition process because the former avoids an extra step of making unstable organyl azides (Scheme 1).…”
Section: Introductionmentioning
confidence: 83%
“…The nickel (Ni) catalyzed azide alkyne [3+2] cycloaddition (NiAAC) has been rarely explored and literature reports reveal only a few Ni-based catalysts employed in AAC. [13][14][15][16] While the use of Raney nickel leads to both 1,4-and 1,5-disubstituted cyclo-adducts, 13 the other ligand-specific and expensive catalytic system (Cp2Ni-Xantphos) can be used for both terminal and internal alkynes preferentially forming 1,5-disubstituted triazole. 14,15 Moreover, the actual catalyst in this case is Ni(Xantphos)2, which is generated in situ and not recoverable.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…expanded the application of their strategy to other functionalized internal alkynes, including cyanoalkynes, thioalkynes and ynamides, all of which could offer desired trisubstituted triazoles ( 75 – 77 ) with exclusive regioselectivities (b–d, Scheme 36). [55] …”
Section: Transition Metal‐catalyzed Cycloaddition Of Azides With Intementioning
confidence: 99%